2022
DOI: 10.1007/s10666-022-09817-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Temperature and Rainfall on Malaria Incidence in Ghana from 2012 to 2017

Abstract: Malaria has a significant impact on the lives of many in Ghana. It is one of the key causes of mortality and morbidity, resulting in 32.5% of outpatient visits and 48.8% of under 5-year-old hospital admissions. Future climate change may impact on this risk. This study aims at estimating the impact of climate variables and health facilities on malaria prevalence in Ghana using regional data from January 2012 to May 2017. This study links data at a regional level on malaria cases with weather data to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Te correlation and multiple regression analyses results show that the number of confrmed cases of malaria in children below fve years increases with an increase in the number of tested cases and average monthly rainfall amounts. Te positive correlation between rainfall and the number of confrmed malaria cases in children is similar to the fndings of Oheneba-Dornyo et al [50] in malaria prevalence in which the Ghanaian population is positively associated with rainfall. However, high amount of rainfall is destructive to breeding sites of mosquitoes which may lead to reduced mosquito populations and subsequent reduction in malaria infections.…”
Section: Resultssupporting
confidence: 84%
“…Te correlation and multiple regression analyses results show that the number of confrmed cases of malaria in children below fve years increases with an increase in the number of tested cases and average monthly rainfall amounts. Te positive correlation between rainfall and the number of confrmed malaria cases in children is similar to the fndings of Oheneba-Dornyo et al [50] in malaria prevalence in which the Ghanaian population is positively associated with rainfall. However, high amount of rainfall is destructive to breeding sites of mosquitoes which may lead to reduced mosquito populations and subsequent reduction in malaria infections.…”
Section: Resultssupporting
confidence: 84%
“…In line with improved conditions for mosquito habitat, rainfall had a positive relationship with P. falciparum seropositivity for all models except for one. This positive relationship has also been noted in multiple malaria studies [ 45 , 46 ]. Air temperature was found to have a consistently negative association with seropositivity.…”
Section: Discussionsupporting
confidence: 74%
“…Lunde et al [ 25 ] examined six different survival models, but again did not address the issue of variability [ 26 ]. Other field-based modelling studies, that do account for daily variability, have shown similar effects of temperature on malaria incidence [ 27 30 ]. Interestingly, for the dry season model, the data indicate that temperature does not have a significant effect.…”
Section: Discussionmentioning
confidence: 89%